2022
DOI: 10.1249/mss.0000000000003049
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated but Not Time-Aligned Response in Myogenic Regulatory Factors Demethylation and mRNA Expression after Divergent Exercise Bouts

Abstract: Introduction: DNA methylation regulates exercise-induced changes in the skeletal muscle transcriptome. However, the specificity and the time course responses in the myogenic regulatory factors DNA methylation and mRNA expression after divergent exercise modes are unknown. Purpose: This study aimed to compare the time course changes in DNA methylation and mRNA expression for selected myogenic regulatory factors (MYOD1, MYF5, and MYF6) immediately after, 4 h after, and 8 h after a single bout of resistance exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The authors reported that CpG sites associated with several metabolic genes exhibited more robust demethylation responses to the higher intensity bout of change-of-direction running versus straight line running. Telles et al [48] more recently examined how resistance exercise, high-intensity interval exercise, or the combination of both affected the mRNA expression and DNA methylation of select myogenic regulatory factors (MYOD1, MYF5, and MYF6). All exercise protocols were reported to promote DNA demethylation of these genes 4 h and 8 h post-exercise, and the mRNA expression of MYOD1 and MYF6 were elevated 4 h following exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that CpG sites associated with several metabolic genes exhibited more robust demethylation responses to the higher intensity bout of change-of-direction running versus straight line running. Telles et al [48] more recently examined how resistance exercise, high-intensity interval exercise, or the combination of both affected the mRNA expression and DNA methylation of select myogenic regulatory factors (MYOD1, MYF5, and MYF6). All exercise protocols were reported to promote DNA demethylation of these genes 4 h and 8 h post-exercise, and the mRNA expression of MYOD1 and MYF6 were elevated 4 h following exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when acute and chronic methylome and transcriptome data were overlapped, ~40% of differentially expressed genes were shown to be associated with altered DNA methylation signatures [24]. Telles et al [48] more recently reported that an interrelated, but not time-aligned response, of myogenic regulatory factor gene demethylation and mRNA expression occurred up to 8 h following resistance exercise and other exercise modalities. However, their analyses were only limited to three genes, and it is notable that all these prior studies examined untrained participants.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when acute and chronic methylome and transcriptome data were overlapped, ~40% of differentially expressed genes were shown to be associated with altered DNA methylation signatures [24]. Telles et al [47] more recently reported that an interrelated, but not time-aligned response, of myogenic regulatory factor gene demethylation and mRNA expression occurred up to 8 hours following resistance exercise and other exercise modalities. However, their analyses were only limited to three genes, and it is notable that all these prior studies examined untrained participants.…”
Section: Insert Table 2 Here Discussionmentioning
confidence: 99%
“…The authors reported that CpG sites associated with several metabolic genes exhibited more robust demethylation responses to the higher intensity bout of change-of-direction running versus straight line running. Telles et al [47] more recently examined how resistance exercise, high-intensity interval exercise, or the combination of both affected the mRNA expression and DNA methylation of select myogenic regulatory factors (MYOD1, MYF5, and MYF6). All exercise protocols were reported to promote DNA demethylation of these genes 4- and 8-hours post-exercise, and the mRNA expression of MYOD1 and MYF6 were elevated 4 hours following exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, endurance training promoted the demethylation of genes involved in angiogenesis or oxidative metabolism, associated with increased gene transcription ( 442 , 443 ), whereas in others there was little effect of HIIT or resistance training on DNA methylation ( 444 ). A recent study reported that despite divergent contractile stimuli (HIIT, endurance and resistance exercise), changes in DNA methylation and mRNA expression in skeletal muscle were largely confined to the late (4–8 h) recovery period and similar between the different exercise challenges ( 445 ). Many of the discrepancies between investigations can likely be explained by the timing of the biopsy ( 446 ), with time course studies suggesting that some DNA methylation changes are retained for up to 48 h after the last training bout ( 442 , 443 ), returning to baseline levels after 72 h ( 444 ).…”
Section: Physiological and Cellular Adaptation To Exercise Training: ...mentioning
confidence: 99%